Pengaruh Analisis Jabatan Terhadap Pencapaian Kinerja Pada Dinas Tenaga Kerja Transmigrasi Dan Sosial Kota Jayapura - Daniel Ayub Dawan (JURNAL EKONOMI, KEUANGAN, PERBANKAN, KEWIRAUSAHAAN DAN KOPERASI, 2020)
The main goal of task analysis is to develop a competent staffing system based on the principle of "right man, right place." The recent occurrence indicates that there are various distinctions between the position and the occupant. As a result, an organization’s performance is less than ideal. This study employs both qualitative and quantitative data analysis approaches. The data analysis strategy utilized in the research process is determined by the research technique used. If we divide the category of research methodologies in social research into two areas, qualitative and quantitative, the data analysis methods utilized are also divided into two groups. The research sample consisted of employees from the Jayapura City Manpower, Transmigration, and Social Service Department. Based on the research findings, the researchers in this study examined and appraised job analyses that influenced performance achievement at the Jayapura City Manpower and Social Service Office. Based on the findings of data processing in the field and matching the results of data processing using SPSS, it can be determined that job analysis has a simultaneous influence on performance attainment at the Jayapura City Manpower and Social Transmigration Service While the findings of the researchers’ research in the discussion suggested that work requirements had a partial impact on the achievement of performance in the setting at the Department of Manpower, Transmigration, and Social Affairs, Jayapura City. According to the study’s findings, job descriptions have a greater influence on enhancing employee performance than other criteria. Job requirements can improve employee performance and are classified as improving the performance of the personnel organization, allowing them to accomplish program goals as intended in the environment at the Jayapura City Manpower and Social Transmigration Office.